2015
DOI: 10.1371/journal.pone.0132716
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Incidence Rates during 1999-2008 and Prevalence in 2008 of Childhood Type 1 Diabetes Mellitus in GERMANY – Model-Based National Estimates

Abstract: AimsTo estimate the national incidence rate and trend of type 1 diabetes (T1DM) in Germany from 1999 to 2008 and the national prevalence in 2008 in the age group 0–14 years.MethodsData were taken from a nationwide registry for incident cases of T1DM in the ages 0–4 years and 3 regional registries (North-Rhine-Westphalia, Baden-Wuerttemberg and Saxony) for incident cases of T1DM in the ages 0–14 years covering 41% of the child population in Germany. The degree of ascertainment was ≥ 97% in all registries. Incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 23 publications
4
49
0
7
Order By: Relevance
“…With regard to diabetes, only 1 case of type 1 diabetes was reported among the 1,595 patients of the safety cohort during the 22-year observational period. Based on an estimated national incidence rate of 22.9/100,000 person-years in German children aged 0–14 years [49], no increased risk of developing diabetes type 1 under GH therapy was identified in our study.…”
Section: Discussionmentioning
confidence: 73%
“…With regard to diabetes, only 1 case of type 1 diabetes was reported among the 1,595 patients of the safety cohort during the 22-year observational period. Based on an estimated national incidence rate of 22.9/100,000 person-years in German children aged 0–14 years [49], no increased risk of developing diabetes type 1 under GH therapy was identified in our study.…”
Section: Discussionmentioning
confidence: 73%
“…Reports on T2D prevalence in childhood and adolescence, however, may refer to groups as follows: 0 to 14 years, 0 to 20 years, 10 to 20 years, or 6 to 15 years, thus rendering comparisons difficult. In spite of this, there is no doubt that the prevalence of T2D in South Germany remains far behind that of type 1 diabetes in the same area reported to be 132.6 (95% CI: 127.2‐138.3) per 100 000 in patients 0 to 14 years …”
Section: Discussionmentioning
confidence: 96%
“…The incidence of type 1 diabetes (T1D) among children and adolescents is rising worldwide . Epidemiological studies have found an annual increase in T1D incidence of 1.5% to 2.4% in various areas of the United States and Canada, 3.3% to 5.9% in various European countries, 4.4% to 5.6% in Asia, and 3.8% in Australia . In a multicenter prospective study that included 20 population‐based registries from 17 countries in Europe (EURODIAB study group), all but 2 registries showed a significant rise in annual incidence ranging from 0.6% to 9.3% .…”
Section: Introductionmentioning
confidence: 99%